A possible novel approach to small iatrogenic colonic perforation during nephrostomy placement - Pedro Laranjeira Barros; Bárbara Oliveira; Rute Pereira; Marco Dores; Aníbal Coutinho; Inês Peyroteo (Urology Case Reports, 2023)
Placement of a percutaneous nephrostomy (PCN), to drain and preserve renal function, is a common urologic procedure in the setting of high urinary obstruction. Colonic perforation is a rare complication, with an incidence of 0.2–0.5%. In these situations, literature advises the withdrawal of the PCN into the colon, ureteral stenting, zero-diet, broad spectrum antibiotics and only to remove the catheter days after. Here we describe the case of a patient in whom a PCN was placed transversing the colon, in whom it was retrieved under endoscopic control, with use of endoclips to control the hemorrhage and close the perforation.